KEPASTIAN HUKUM TERHADAP PERLINDUNGAN KARYA CIPTA TARI JAIPONGAN DI WILAYAH JAWA BARAT - Sulistijono Sulistijono (SASI, 2020)
The diversity possessed by the Indonesian nation starts from its various ethnicities, languages and cultures, Of course, this is inseparable from the participation of the community in developing the natural wealth owned by Indonesia, one of Indonesia's cultural wealth is the culture of dance in the West Java region, namely the jaipongan dance. Dance is a branch of the performing arts that has legal protection by copyright. The research method uses descriptive analytical research type, which is a study that describes or describes something that has happened or is currently taking place in a certain place and at a certain time, describing or describing the problems that have occurred.The analysis of the authors in this study, that the form of protection of Jaipongan dance creations inWest Java is still limited to regulation because economic rights have not been realized properly so that legal certainty is not realized. The conclusion is to obtain legal certainty regarding the economic rights obtained from his works in the form of royalties, a special collective management agency for dance can be formed and the need for recording requirements procedures related to various dances that can be recorded.